BENTUK PARTISIPASI MASYARAKAT DALAM PROGRAM RUMAH BAHASA KOTA SURABAYA PADA MASA PANDEMI COVID-19 - Mega Selvina Agusta; Lunariana Lubis; Deasy Arieffiany (Aplikasi Administrasi: Media Analisa Masalah Administrasi, 2020)
Surabaya Language House Program is established by the Mayor of Surabaya Tri Rismaharini in 2014 aimed at improving the quality of human resources by learning foreign languages for free. The Covid-19 pandemic that hit the world in early 2020 made the Language House Program temporarily suspended and began to be held again using online media. This study aims to determine the form of community participation in the Language House Program during Covid-19. This study uses the theory of Keith Davis in Sastropoetro (1988). The method uses qualitative case study approach. Data collection techniques uses documentation, online interviews, online observations. The results indicate that the form of mind participation is in online classes so that Language House Program does not completely stop. The form of energy participation carried out is by tutors in teaching language through online media. The form of mind and energy participation is done by making syllabus which will be taught in each class through discussions. The form of skill participation is to develop the language skills by taking language certification and teaching practices.